Automated solid-phase peptide synthesis to obtain therapeutic peptides - Mäde, Veronika; Els-Heindl, Sylvia; Beck-Sickinger, Annette G. (Beilstein Journal of Organic Chemistry, 2014)
The great versatility and the inherent high affinities of peptides for their respective targets have led to tremendous progress for therapeutic applications in the last years. In order to increase the drugability of these frequently unstable and rapidly cleared molecules, chemical modifications are of great interest. Automated solid-phase peptide synthesis (SPPS) offers a suitable technology to produce chemically engineered peptides. This review concentrates on the application of SPPS by Fmoc/t-Bu protecting-group strategy, which is most commonly used. Critical issues and suggestions for the synthesis are covered. The development of automated methods from conventional to essentially improved microwave-assisted instruments is discussed. In order to improve pharmacokinetic properties of peptides, lipidation and PEGylation are described as covalent conjugation methods, which can be applied by a combination of automated and manual synthesis approaches. The synthesis and application of SPPS is described for neuropeptide Y receptor analogs as an example for bioactive hormones. The applied strategies represent innovative and potent methods for the development of novel peptide drug candidates that can be manufactured with optimized automated synthesis technologies.
Keywords: automated synthesis; automation; lipidation; PEGylation; peptide drugs; solid-phase peptide synthesis; therapeutic peptides